Peer review of the pesticide risk assessment of the active substance Pythium oligandrum strain B301 - European Food Safety Authority (EFSA); Fernando Álvarez; Maria Arena; Domenica Auteri; Sofia Batista Leite; Marco Binaglia; Anna Federica Castoldi; Arianna Chiusolo; Angelo Colagiorgi; Mathilde Colas; Federica Crivellente; Chloe De Lentdecker; et al. (EFSA Journal, 2024)
Abstract The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State Belgium for the pesticide active substance Pythium oligandrum strain B301 and the considerations as regards the inclusion of the substance in Annex IV of Regulation (EC) No 396/2005 are reported. The context of the peer review was that required by Regulation (EC) No 1107/2009 of the European Parliament and of the Council. The conclusions were reached on the basis of the evaluation of the representative uses of Pythium oligandrum strain B301 as a resistance inducer/elicitor to control trunk diseases on grapevines. The reliable endpoints, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.